Viktorjev spodmol in Mala Triglavca = Viktorjev spodmol and Mala Triglavca Prispevki k poznavanju mezolitskega obdobja v Sloveniji = Contributions to understanding the Mesolithic period in Slovenia - Turk, Ivan (Opera Instituti Archaeologici Sloveniae, 2004)
The monograph, the first regarding the Mesolithic in Slovenia, presents a discussion of two exceptionally rich sites in the Karst in western Slovenia: Viktorjev spodmol and Mala Triglavca. Viktorjev spodmol is a newly discovered site, where test excavation have only been done, while research is underway at Mala Triglavca already a while.The compilation primarily presents a detailed review of Viktorjev spodmol. Individual chapters address the topic of microlithic tools attributed to the Sauveterrien-Castelovien complex, their typology and relations with other sites from this complex, and with a special emphasis on the chronology and chronological correlations between Mesolithic sites in northern Italy, including the Trieste karst, and western Slovenia. The remaining chapters systematically present rare vegetal remains, the exceptionally rich collections of mollusc's fauna, ectothermic vertebrates and small mammals as well as the remains of large mammals.Mala Triglavca is equally profuse, although it is discussed only summarily in this monograph, and with an emphasis on Mesolithic artefacts. From among these finds, the numerous trapezes are particularly noteworthy, and from among the more rare finds at least the bone whistle and flute. Also noteworthy are the rare human remains discovered at both sites.